2009
DOI: 10.1111/j.1532-950x.2009.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Behavior and Clinical Outcome of 25 Dogs with Canine Appendicular Chondrosarcoma Treated by Amputation: A Veterinary Society of Surgical Oncology Retrospective Study

Abstract: The overall prognosis for appendicular chondrosarcoma is better than that of appendicular osteosarcoma treated by amputation alone or in combination with chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 5 publications
2
32
0
7
Order By: Relevance
“…Any tumour causing pain, affecting normal function or which is ulcerated/bleeding can be treated with palliative surgery. Examples include soft tissue sarcomas or mast cell tumours in locations where margins are not achievable or curative intent surgery has been declined, and oral tumours such as melanoma (Verstraete 2005, Waltman and others 2007, Kramer and others 2008, Liptak and others 2008a, b, Morello and others 2008, Stefanello and others 2008, Stratmann and others 2008, Borrego and others 2009, Farese and others 2009, Mayer and others 2009, Arzi and Verstraete 2010, Nelissen and White 2012, Tuohy and others 2012, 2014, Bray and others 2014, Cameron and others 2015, Garneau and others 2015, Matz 2015, Wendelburg and others 2015) (Figs 1 to 3). Thorascopic procedures may allow for faster postoperative recovery (Mayhew and Friedberg 2008, Peláez and others 2008, Naan and others 2013, Ployart and others 2013, Shaver and others 2015).…”
Section: Surgerymentioning
confidence: 99%
“…Any tumour causing pain, affecting normal function or which is ulcerated/bleeding can be treated with palliative surgery. Examples include soft tissue sarcomas or mast cell tumours in locations where margins are not achievable or curative intent surgery has been declined, and oral tumours such as melanoma (Verstraete 2005, Waltman and others 2007, Kramer and others 2008, Liptak and others 2008a, b, Morello and others 2008, Stefanello and others 2008, Stratmann and others 2008, Borrego and others 2009, Farese and others 2009, Mayer and others 2009, Arzi and Verstraete 2010, Nelissen and White 2012, Tuohy and others 2012, 2014, Bray and others 2014, Cameron and others 2015, Garneau and others 2015, Matz 2015, Wendelburg and others 2015) (Figs 1 to 3). Thorascopic procedures may allow for faster postoperative recovery (Mayhew and Friedberg 2008, Peláez and others 2008, Naan and others 2013, Ployart and others 2013, Shaver and others 2015).…”
Section: Surgerymentioning
confidence: 99%
“…The dog developed a harsh cough and became anorectic 15 weeks after surgery; thoracic radiography revealed changes compatible with pulmonary metastasis and the patient was euthanatised (Flanders and others ). However, more recent studies have reported good overall median survival time of dogs treated for skeletal and extraskeletal CSA(Pirkey‐Ehrhart and others , Dernell and others , Waltman and others , Liptak and others , Farese and others ). Survival was significantly associated with tumour grade, with dogs with tumour grade of 1, 2 and 3 having median survival time of 6, 2·7 and 0·9 years, respectively (Farese and others ).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have reported good overall median survival time of dogs treated for skeletal and extraskeletal CSA(Pirkey‐Ehrhart and others , Dernell and others , Waltman and others , Liptak and others , Farese and others ). Survival was significantly associated with tumour grade, with dogs with tumour grade of 1, 2 and 3 having median survival time of 6, 2·7 and 0·9 years, respectively (Farese and others ). Wide surgical excision significantly improves survival time for dogs with CSA of non‐nasal bony sites, but does not affect the likelihood of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high similarity at the clinical, histopathological and molecular levels, spontaneous tumours in dogs are considered excellent models for human diseases, representing an alternative to rodents for studying cancer biology and therapy . Canine osteosarcoma (OSA) represents the most common primary malignant bone tumour in dogs, accounting for more than 80% of all bone tumours; it is locally aggressive and is characterized by a high metastatic potential and poor prognosis . Furthermore, the role of several tyrosine kinase receptors (TKRs) in the pathogenesis of canine OSA was recently demonstrated, which reveals the utility of tyrosine kinase inhibitors (TKIs) against specific targets …”
Section: Introductionmentioning
confidence: 99%